Application of graph theory for the calculation of power supply systems. Optimal location of the substation into the grid - Kozyrsky, V.; Gnuchij, Y.; Guy, A.; Kostyuk, V. (Енергетика і автоматика, 2015)
A rationale for the application of graph theory to rationalize the structure of the system power supply voltage of the middle class. Performed theoretical and practical search for the center of the graph, and optimization implemented in the electrical substation location. The tasks of further research.